Mutual effect of U(vi) and Sr(ii) on graphene oxides: evidence from EXAFS and theoretical calculations. Issue 5 (3rd April 2017) - Cheng, Wencai; Ding, Congcong; Wu, Qunyan; Wang, Xiangxue; Sun, Yubing; Shi, Weiqun; Hayat, Tasawar; Alsaedi, Ahmed; Chai, Zhifang; Wang, Xiangke
Abstract : The competitive interaction of U(vi ) and Sr(ii ) on graphene oxides (GOs) was studied by batch techniques, EXAFS analysis and DFT calculations. Abstract : The competitive interaction of U(vi ) and Sr(ii ) on graphene oxides (GOs) was studied by batch techniques, EXAFS analysis and DFT calculations. The batch results indicated that decreased sorption of Sr(ii ) on GOs was observed at C [U(vi )] < 0.2 mmol L −1 and enhanced sorption of Sr(ii ) was found at C [U(vi )] > 0.2 mmol L −1, whereas the presence of Sr(ii ) did not affect U(vi ) sorption on GOs. The increased sorption of Sr(ii ) at C [U(vi )] > 0.2 mmol L −1 resulted from the new available sites provided by the precipitated U(vi ) or adsorbed hydrolyzed U(vi ) species according to EXAFS analysis. The occurrence of a U–C shell in the absence/presence of Sr(ii ) indicated that U(vi ) tended to form inner-sphere surface complexes with GOs. For the Sr(ii ) interaction, a Sr–C shell was observed at a low U(vi ) concentration, but not formed at a high U(vi ) concentration, indicating the shift of inner-sphere to outer-sphere surface complexes with increasing U(vi ) concentration. According to DFT calculation, the binding energy of GO–U(vi ) ( e.g., −40.3 kcal mol −1 for inner-sphere coordination) was significantly lower than that of GO–Sr(ii ) (−16.4 kcal mol −1 ), demonstrating that U(vi ) was preferentially bound to GOs relative to Sr(ii ). These findings can provide a reliable prediction of the transport and fates of U(vi ) and Sr(ii ) at the water–GO interface and open doorways for the application of GOs.